Two-phase structure in the Bose–Einstein condensate dark matter model - Nazarenko, Andriy (6-th International Conference “Statistical Physics: Theory and Computer Simulations”, 2025)
Toaccuratelydescribeastrophysicalobservablesinmodelsofself-gravitating Bose–Einstein condensate dark matter (BEC DM), it is essential to incorporate the self-interaction (SI) among ultralight bosons. In particular, simultaneously including two- and three-particle SIs gives rise to novel phenomena—a twophase structure and an associated quantum ýrst-order phase transition at zero temperature [1,2]. Replacing the polynomial SI with an axionlike periodic potential not only reproduces these results via non-perturbative solutions of the stationary Gross–Pitaevskii equation [3] but also complicates the phase diagram by the appearance of additional, including unstable, phases and transitions [4]. [eaxionlikeSIcanbealsoinvolvedintheformationofcomposites— speciýcally, dimers—from DM particles [3]. Applying this framework to DM-dominated dwarf galaxies, such as NGC2366,reveals aýrst-order phase transition (PT1) driven by quantum uctuations in particle density. [is transition marks an abrupt shi from a diôuse state to a denser conýguration, even though the DM parameters of NGC 2366 suggest a continuous, supercritical behavior. Notably, PT1 also serves as a thermodynamicindicatorthatdistinguishes betweenstable andunstableconýgurations. When adensephasenucleus(core) forms—reaching a threshold of about 12%ofthe total mass—the enhanced gravitation provides stability against uctuations. In comparison, the dense DM of NGC2366comprisesroughly19%of the mass while occupying only 4.7% of its total volume [4].